The Structure of Macrozoobenthos Community as a Bioindicator of Water Quality in Gilimanuk Bay, Jembrana Regency, Bali - Ndale, Yohana Christanti; Restu, I Wayan; Wijayanti, Ni Putu Putri (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
Gilimanuk Bay is a water area located in Melaya District, Jembrana Regency, West Bali Region. In this area, there are development and human activities that have an impact on the quality of the waters so that they interfere with the life of organisms such as macrozoobenthos. Macrozoobenthos can be the bioindicator that determining the condition in a water area. The decline of the macrozoobenthos community structure is an indicator of a disturbance in the ecosystem in these waters. The purpose of this research to know how community structure of macrozoobenthos and the condition of the water quality in Gilimanuk Bay. This research was conducted in June to July 2020. The research used the quantitative descriptive method, with 3 of the research stations. Based on the result of the research, it has found 45 species of macrozoobenthos that included from 5 classes, there are Gastropods, Bivalves, Crustaceans, Polychaeta and, Sipunculidea. The highest total abundance was at station 3, namely 534.33 ind/m 2 , station 1 is 522.00 ind/m 2 and the lowest abundance is at station 2, namely 371.33 ind/m 2 . The diversity index obtained was classified as moderate, which ranges from 1.53-1.89, the uniformity index is classified as moderate, which ranges from 0.47-0.57, while the dominance index is low to moderate, which ranges from 0.29-0.44. Based on the macrozoobenthos community structure and the interrelation with water quality, Gilimanuk Bay is classified as moderately polluted waters.